The Concept of Time in Mulla Sadra's Philosophy - Al Walid, Khalid; Ain Norman, Nurul; Miri, Mohsen (Jurusan Aqidah dan Filsafat Islam Universitas Negri Sunan Gunung Djati Bandung, 2024)
This article explains the concept of time in Mulla Sadra's Philosophy. Mulla Sadra is a philosopher who succeeded in establishing the third school of thought in Islamic philosophy. A fundamental problem in the philosophy of time is whether time is a real entity or merely a product of human perception of external reality. Does time exist because of external objects, or does it emerge alongside the presence of the possible being (al-Mumkin)? An analytical approach is used in this article to explore the structure of the concept of time developed by Mulla Sadra and the specific aspects that distinguish it from the views of previous philosophers.Mulla Sadra bases his explanation of time on the principles of Ashalat al-Wujud (the Primacy of Existence), Tasykik al-Wujud (the Gradation of Existence), and Harakat al-Jawhariyyah (the Essential Motion).For Mulla Sadra, time is included in Amr al-Wujudi, namely an element that is included in the part of being and being is a Single, gradative essence. Time is essentially Single with all physical objects so that everything that is physical is at the same time also enveloped by time.